High prevalence and risk factors of fascioliasis in cattle in Amazonas, Peru - Diaz-Quevedo C. (2021)
This study was carried out within the framework of the Doctoral Program in Sciences for Sustainable Development financed by the National Fund for Scientific and Technological Development and Technological Innovation (FONDECYT) and the World Bank Group. CDQ was funded by FONDECYT 03-2018- FONDECYT/BM-DOCTORATE PROGRAMS IN STRATEGIC AND GENERAL AREAS- ?Doctorate in Sciences for Sustainable Development?. JRT, SMC, HF and RT are funded by Contrato N? 09-2019-FONDECYT-BM-INC.INV. Funding for open access publishing: Universidad Pablo de Olavide/CBUA. The authors wish to thank Cecilia Pajuelo, Carla Montenegro and Rocio Jara Vilca for their contribution in the laboratory procedures.